2016
DOI: 10.1098/rspb.2015.2548
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence is consistent with a prominent role of spatial memory in complex navigation

Abstract: The ability to learn about the spatial environment plays an important role in navigation, migration, dispersal, and foraging. However, our understanding of both the role of cognition in the development of navigation strategies and the mechanisms underlying these strategies is limited. We tested the hypothesis that complex navigation is facilitated by spatial memory in a population of Chrysemys picta that navigate with extreme precision (+3.5 m) using specific routes that must be learned prior to age three. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 50 publications
(167 reference statements)
4
33
0
Order By: Relevance
“…Building on this study, we recently treated freely navigating painted turtles with scopolamine to determine if ACh facilitated migratory navigation. [98] Scopolamine disrupted the navigation ability of experienced adults, but not juveniles learning to navigate. We followed up this work by repeating the experiment with a specific M1 ACh receptor antagonist and found that blocking these receptors not only disrupted the recollection of spatial memories of migrating adults, but prevented naive turtles from forming such memories and learning migratory routes.…”
Section: Manipulation Of Biochemical Processes In the Brain Implies Cmentioning
confidence: 94%
See 2 more Smart Citations
“…Building on this study, we recently treated freely navigating painted turtles with scopolamine to determine if ACh facilitated migratory navigation. [98] Scopolamine disrupted the navigation ability of experienced adults, but not juveniles learning to navigate. We followed up this work by repeating the experiment with a specific M1 ACh receptor antagonist and found that blocking these receptors not only disrupted the recollection of spatial memories of migrating adults, but prevented naive turtles from forming such memories and learning migratory routes.…”
Section: Manipulation Of Biochemical Processes In the Brain Implies Cmentioning
confidence: 94%
“…Treatment with scopolamine reduced maze learning compared to controls, demonstrating a role of ACh in spatial memory recall in painted turtles. Building on this study, we recently treated freely navigating painted turtles with scopolamine to determine if ACh facilitated migratory navigation . Scopolamine disrupted the navigation ability of experienced adults, but not juveniles learning to navigate.…”
Section: Integrating Behavior and Mechanism Enhances Our Understandinmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological manipulation with scopolamine, a general muscarinic acetylcholine receptor (AChR) antagonist, successfully blocks the formation and recall of spatial memories during laboratory experiments of navigation [ 14 , 16 – 18 ]. Moreover, scopolamine alters the precision of animal movements in the field during migration [ 19 , 20 ], supporting the role of the cholinergic system, and potentially spatial cognition, in large-scale migratory movements. Such studies have been critical to our understanding of how the brain produces spatially explicit memories, and how such memories influence navigation behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…alterations in thirst, light sensitivity, and motivation) with a generalist antagonist (reviewed by Klinkenberg & Blokland [ 15 ]), it is possible that the disruptions in navigation observed during these migratory studies (e.g. [ 19 , 20 ]) could have resulted from the manipulation of non-spatial, non-cognitive processes such as sensation, perception, or attention. Thus, such studies could not definitively conclude that observed changes in navigation were solely due to a manipulation of spatial memory.…”
Section: Introductionmentioning
confidence: 99%